ECMO Support in Pediatric Populations with the Newborn ECMOLife Centrifugal Pump - Carlo Pace Napoleone; Ignazio Condello; Maria Teresa Cascarano; Enrico Aidala; Licia Peruzzi; Isabella Molinari; Cristina Rivoldini; Maria Stella Di Carlo; Stefania Iannandrea; Enrico Bonaveglio (Medicina)
Background and Objectives: Pediatric ECMO is a valid support mechanism for refractory cardiac and/or respiratory failure. Magnetic levitation technology applied to the centrifugal pump has reduced the hemolysis caused by this procedure, which can be particularly dangerous, especially in neonates and small children. ECMOLife, a new magnetic levitation centrifugal pump, has been introduced for these patients. Materials and Methods: Four patients were supported with the ECMOLife System in a newborn setting, with veno-venous application in two cases and veno-arterial in the other two. All parameters related to pump functioning, anticoagulation, hemolysis, and inflammation were recorded for the duration of the support. Results: All patients survived the procedure, in three cases achieving recovery, while one veno-arterial ECMO was switched to VAD, and then the patient underwent heart transplantation. All recorded parameters were compatible with clinical conditions. In particular, free haemoglobin was close to 0 g/L in all recorded samples. The possibility of monitoring pump functioning parameters, venous and arterial O2 saturation, and venous and arterial pressures creates an opportunity to check the adequacy of mechanical support for the clinical condition of the patient. Conclusions: This is the first reported experiment in a newborn setting with ECMOLife mechanical support. At present, ECMOLife represents the only system with a newborn and pediatric pump, allowing for the continuous monitoring of perfusion and hemodynamic parameters, with a large number of facilities for transportation available.